Identification of 2-Cys Peroxiredoxin (BmTPx-2) as Antioxidant Active Molecule from Babesia microti - Hai, Xunan; Zhang, Houshuang; Wang, Zhonghua; Gong, Haiyan; Cao, Jie; Zhou, Yongzhi; Zhou, Jinlin (Frontiers in Microbiology, 2017)
Peroxiredoxins (Prxs) are a family of antioxidant enzymes that reduce peroxides in the presence of thioredoxin, thioredoxin reductase, and nicotinamide adenine dinucleotide phosphate (NADPH) to resist oxidative stress. In this study, we identified and isolated a 2-Cys Prx designated as ‘BmTPx-2’ from Babesia microti, with a full-length cDNA of 826 bp and an open reading frame of 756 bp, which encodes a 251-amino acid protein. BLAST analysis demonstrated that BmTPx-2 shows the typical features of members of the 2-Cys Prx family, which includes harboring two conserved VCP motifs with Cys101 and Cys221 conserved cysteine residues. Recombinant BmTPx-2 was expressed in Escherichia coli and analyzed by western blot. The antioxidant activity of BmTPx-2 was demonstrated using a mixed-function oxidation system and oxidation of NADPH. Furthermore, BmTPx-2 mRNA expression level in parasites at the erythrocytes and tick stages were analyzed by real-time fluorescence quantitative PCR. Peak BmTPx-2 mRNA transcription was detected 8 days after infection at the erythrocyte stage, but not at the tick stage. Taken together, this study characterized BmTPx-2 from B. microti as an antioxidant molecule that was specifically transcribed at the erythrocyte stage.